Perbaikan dan Perancangan Fitur Review Produk Dalam Upaya Meningkatkan Aktivitas Pengguna Untuk Memberikan Ulasan di Aplikasi Zalora - Utami, Mutiara Gunawan; Junia, Annisa Aghniarahma (Peneliti.net, 2024)
Increasing use of the internet via smartphones is used by marketplace service providers to provide a place for sellers to sell goods and services via the internet by creating a Mobile App. Zalora is an online fashion and beauty store that offers a wide range of clothing, accessories, shoes and beauty products for men and women. As a company engaged in online trading, Zalora continues to try to meet consumer needs for fashion products. This study uses a qualitative analysis approach by conducting in-depth interviews with five users of the Zalora application to understand the phenomena experienced by research subjects, such as behavior, perceptions, motivation, action, and so on. The selection of interview participants was carried out using convenience sampling considering the convenience of the researcher. There is a problem found, namely user participation in providing reviews and feedback on the products purchased is still low. Recommendations that can be given from this research are to make photo & video input features in providing product reviews, provide rewards in the form of points for users who have provided reviews, and optimize the Pop up review and Notification features.